Heat as medicine - a study of the ceiling retrofit programme in South African low cost housing - Kirsten, Sean Louis (School of Economics, 2015)
Exploring the energy saving and efficient intervention options available to governments, Winkler et al (2002) measured the energy cost-benefits of different interventions in low cost housing across South Africa. These interventions included installing insulated ceilings (retrofitting), roof insulation, partitions, wall insulation, window insulation, solar water heaters (SWH) and compact fluorescent lights (CFL's). Of these interventions, wall insulations and ceiling installations were the most cost-effective interventions. This approach was coined "Heat as medicine" by Howden‐Chapman (2011) and a CBA conducted by his team concluded a 2:1 benefit to cost ratio (B:C) from the insulation process (IEA, 2011). Mathews and van Wyk (1996) found that by installing a ceiling in a low cost house, a 74% saving in energy consumption can be made during winter and Spalding-Fecher et al (2002) found a R781 saving in energy per year per household from ceiling installations. With ceilings having such a substantial cost-effective impact on energy efficiency, this paper will be focusing on the ceiling retrofitting intervention in addressing energy poverty. Surprisingly, solar water heater interventions offer a much smaller net benefit, as a result of high installation costs and increased usage of water. Having attended conferences on this topic and engaged with low-cost house residents in the Western Cape, the SWH intervention is often seen by the households as a luxury item, which they would happily exchange for more direct benefits such as ceilings and affordable and energy-saving cooking stoves.